Pengaruh Fasilitas terhadap Kepuasan Pelanggan pada Usaha Pondok Parsotoan Sidojadi 2 Panyabungan Kabupaten Mandailing Natal - Ahmad Siddiq Pulungan; Andy Hakim; Rizka Ar Rahmah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The Effect of Facilities on Customer Satisfaction at Pondok Parsotoan Sidojadi 2, Panyabungan, Mandailing Natal Regency.”This study examines the effect of facilities on customer satisfaction at Pondok Parsotoan Sidojadi 2, Panyabungan. Facilities include infrastructure, amenities, and conveniences that support business operations, while customer satisfaction refers to the feelings of pleasure or disappointment experienced by customers based on the comparison between their expectations and actual experiences with products or services. The research problems involve inadequate facilities, such as the absence of Wi-Fi and a children’s playground, a small prayer room, limited parking space, narrow stairs, and less aesthetic décor, which reduce customer satisfaction. This study uses a quantitative method with data collected through observation and questionnaires from 96 respondents. Data analysis was conducted using SPSS 25.0, including validity, reliability, normality, heteroscedasticity, simple linear regression, t-test, determination test, and correlation analysis. The t-test results show thitung = 28.981 > ttable = 1.661, indicating that facilities have a positive and significant effect on customer satisfaction. The R Square value of 0.899 (89.9%) and R of 0.948 demonstrate a very strong relationship.